Pemberian Mulsa Alang-Alang (Imperata Cylindrica) untuk menekan gulma pada Pertumbuhan dan Hasil Tanaman Kedelai (Glycine max L. Merill) - Soverda, Nerty (Jurnal Agro Teknologi Tropika, 2015)
One of the much-needed agricultural commodities in Indonesia is soybeans after maize and rice, both as a humanfood, animal feed and industrial raw materials. However, in the development of soybean plants some issues related toagro-ecosystem for planting must be overcome, one of which is not optimal weed management. Competition betweencrops and weeds can be overcome one of which is to provide soil cover (mulch) that can suppress the growth of weeds.The purpose of this research is to test the effectiveness of multiple doses of organic mulch reeds to its ability to suppressweed growth and yield of soybean plants. Under these conditions, the specific target of this research is to get a dose oforganic mulch reeds effective in suppressing weeds in soybean. In addition, to obtain soybean plants were healthy andfree of synthetic herbicides towards organic farming. The results of this study are expected to provide information tofarmers in the use of organic waste can be used as a ground cover or mulch to suppress weeds in soybean plants. Underthese conditions, the specific target of this research is to get a dose of organic mulch reeds effective in suppressing weedsin soybean. In addition, to obtain soybean plants were healthy and free of synthetic herbicides towards organic farming.The results of this study are expected to provide information to farmers in the use of organic waste can be used as aground cover or mulch to suppress weeds in soybean plants. In this experiment to test the effectiveness of various dosesof Reed mulch to suppress weed growth. Besides, community coefficient test, analysis of vegetation (SDR value of early,middle and SDR SDR end), weight broadleaf weeds, narrow leaves and type of puzzle-tekian. Plant growth (plantheight, shoot dry weight, number of pods containing, weight of 100 seeds, and soybean crops). The experiment wasconducted by using a randomized block design. Through this study it was found that the dose of mulch reeds that can beapplied as a soil cover (mulch) on soybean planting is at a dosage of 15 tons ha -1 (D3) and 20 tons ha -1 (D4).